2020
DOI: 10.5194/esd-2020-8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Dynamical Systems Characterisation of Atmospheric Jet Regimes

Abstract: Abstract. Atmospheric jet streams are typically separated into primarily eddy-driven, or polar-front jets and primarily thermally-driven, or "subtropical" jets. Some regions also display merged jets, resulting from the (quasi) co-location of the regions of eddy generation with the subtropical jet. The different locations and driving mechanisms of these jets issue from very different underlying mechanisms, and result in very different jet characteristics. Here, we link our understanding of the dynamical jet mai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…These metrics are related to the intrinsic predictability of the atmosphere and therefore to the stability (here in the context of atmospheric variability) of the flow: a highly persistent (low θ), low-dimensional (low d) state will be more stable than a low-persistence (high θ), high-dimensional (high d) one (Messori et al, 2017). This approach has been applied to various atmospheric fields (e.g., Faranda et al, 2019a;Messori et al, 2021). Indeed, it has been shown that d and θ can offer a dynamical characterization of synoptic systems over several geographical regions (Faranda, Alvarez-Castro, et al, 2017;Hochman et al, 2019;Hochman, Alpert, et al, 2020).…”
mentioning
confidence: 99%
“…These metrics are related to the intrinsic predictability of the atmosphere and therefore to the stability (here in the context of atmospheric variability) of the flow: a highly persistent (low θ), low-dimensional (low d) state will be more stable than a low-persistence (high θ), high-dimensional (high d) one (Messori et al, 2017). This approach has been applied to various atmospheric fields (e.g., Faranda et al, 2019a;Messori et al, 2021). Indeed, it has been shown that d and θ can offer a dynamical characterization of synoptic systems over several geographical regions (Faranda, Alvarez-Castro, et al, 2017;Hochman et al, 2019;Hochman, Alpert, et al, 2020).…”
mentioning
confidence: 99%